Representing indigenous cultures: Alaska Native contemporary art exhibits in Anchorage - Biddison, Dawn (Études/Inuit/Studies)

(untitled) (Association Inuksiutiit Katimajiit Inc., 2004)
AbstractIn this article, I evaluate how Alaska Native contemporary art is presented to the public by examining artists’ perspectives, artwork exhibits and viewer reception of the art. My goal is to substantiate the need to critically address how Alaska Native cultures are represented at museum and public art venues in Anchorage, Alaska. In particular, I seek to emphasize the importance of creating contextualized presentations of Alaska Native art using multiple perspectives and interpretative media based on collaboration between exhibitors and Native artists and communities. More inclusive informative presentations can begin to address the differing requirements of a variety of audiences, utilize the critical attention given to Native American and Euro-American art elsewhere, and provoke a re-thinking of stereotyped preconceptions that continue to diminish the accomplishments of Alaska Native artists and limit perceptions of Alaska Native cultures.